Psychometric properties of the mental health continuum-short form in Iranian adolescents - Yousefi Afrashteh, Majid; Janjani, Parisa (Frontiers in Psychology, 2023)
Background: Psychological tests are necessary to assess and assess the mental state of individuals. Mental health is one of the important psychological indicators and is increasingly considered as having various aspects of well-being. The Mental Health Continuum-Short Form (MHC-SF) is a 14-item instrument that assesses mental health, focusing on emotional, psychological, and social well-being. The present study examined the psychometric properties of the Persian version of the MHC-SF among adolescents, focusing on its factor structure, internal consistency, construct validity, and gender measurement invariance. Methods: The population of this study was Iranian adolescents between 11 and 18 years old who were enrolled in the seventh to twelfth grades. A convenience sample of 822 Adolescents from four large cities in the Iran (Tehran, Zanjan, Hamedan and Ghazvin) participated in the present study. Questionnaires were completed online. Statistical analyses to evaluate the factor structure, internal consistency, construct validity, gender and age factorial invariance were performed in SPSS and LISREL. Results: The results of confirmatory factor analysis supported the 3-factor structure of MHC-SF (emotional, psychological, and social well-being). Reliability was confirmed by Cronbach's alpha method and composite reliability (>.7). Measurement invariance were confirmed among girls and boys. Convergent and divergent validity were also evaluated and confirmed by correlating the test score with similar and different tests. Conclusion: This study examined and confirmed the psychometric properties of MHC-SF in the Iranian adolescent community. This instrument can be used in psychological research and diagnostic evaluations.